1997
DOI: 10.1177/135245859700300405
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus vaccination of patients with multiple sclerosis

Abstract: Prior to vaccination with a trivalent influenza vaccine (AT/Texas, AB/Beijing, and BP/Panama), sera from 19 MS patients had a significantly higher mean level of antibody than 9 normal subjects to AT strain of influenza, but not to AB or BP strains. After Flu vaccination, the mean anti-AT and anti-AB antibody titers significantly increased 4-fold in 11 MS patients and 9 normal subjects. The ratio of MS responders (6/11), however, was lower than normal (8/9). The mean PBL proliferative response to the Flu antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…Moreover, De Keyser et al have shown that influenza infection increases relapse risk whereas patients vaccinated against influenza had a lower risk of relapse (24). Many, but not all, studies have shown that influenza vaccination inhibits relapse (35). Thus, these data suggest that influenza infection may promote exacerbation of MS symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, De Keyser et al have shown that influenza infection increases relapse risk whereas patients vaccinated against influenza had a lower risk of relapse (24). Many, but not all, studies have shown that influenza vaccination inhibits relapse (35). Thus, these data suggest that influenza infection may promote exacerbation of MS symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…It is of interest that T cells from multiple sclerosis patients reportedly produce less TGF-␤1 in culture than do T cells from normal individuals (54). We propose that the genetic engineering of self-reactive T cells with latent TGF-␤ may represent a clinically viable approach to the treatment of autoimmune diseases.…”
Section: Figmentioning
confidence: 99%
“…Three randomized, placebo-controlled trials (Class I, Class II evidence), [20][21][22] one casecrossover (Class III evidence), 19 and seven cohort studies (Class II, Class IV evidence) 10,11,[23][24][25][26][27][28] were identified (see table 2). For each of the three randomized, controlled trials, the rate difference for early MS exacerbation (3 to 4 weeks after vaccine/placebo), for late exacerbation (4 to 6 months after vaccine/ placebo), and for occurrence of influenza was estimated and combined in a meta-analysis (figure).…”
Section: Does Vaccination Increase the Risk Of Exacerbations Of Ms Amentioning
confidence: 99%
“…10,17,20,21 Two randomized controlled trials on influenza vaccine reported influenza episodes during a 6-month follow-up after immunization (see table 2). None of these studies reported data regarding antibody response to vaccine.…”
Section: Are Vaccines As Effective In Patients With Ms As In the Genementioning
confidence: 99%
See 1 more Smart Citation